(untitled) (Fiep Bulletin - online, 2015)
The alterations in body temperature(BT) are responsible for diverse organic reactions. The intention of this study is to verify if loss of corporal fluids in exercises practised in the water occurs and to detect possible alterations in the sanguineous components. For the study had been evaluated 12 men with average age of 19,25 years, swimming practitioners. They had been folloied during a training with duration of 1H38minutes. The measures of weight corporal(PC) and collection of blood and piss had been carried through before and after the training and had been compared. The results had shown reduction of the average PC, increase in the evaluated density of piss in 10/13, reduction in the evaluated PH in 5/13, increase in the number of peripheral platelets number in 10/13 evaluated and average white globule increase of 110,8%.